Administration Of Emprit Ginger Extract (Zingiber Officinale Rosc.) Effect On Cholesterol Reduction In Students Suffering From Hypercholesterolemia - Pasaribu, Ummi Rachmi; Yenita, Yenita (Buletin Farmatera, 2025)
Abstract: Hypercholesterolemia is one of the lipid disorders that is usually characterized by an increase in cholesterol levels in the blood to above 200 mg/dL. The prevalence of hypercholesterolemia in the world is around 45% while in Southeast Asia it is around 30% and in Indonesia it reaches 35%. Currently, people with hypercholesterolemia are not only adults or the elderly, but many children and adolescents have experienced hypercholesterolemia due to their lifestyle. Emprit ginger (Zingiber officinale Rosc.) or small ginger is a ginger used for spices, beverage raw materials, and herbal medicine. The main ingredients in ginger are shogaol and gingerol which are flavonoid compounds. The decrease in cholesterol levels is influenced by flavonoid and polyphenol compounds that prevent free radicals, have a hypocholesterol effect that inhibits the enzyme HMG-CoA reductase.  This study aims to find out whether ginger emprit can lower cholesterol levels in students suffering from hypercholesterolemia. The research method used was quantitative with a research design using pre-experimental (pretest and posttest) on 61 people suffering from hypercholesterolemia and a statistical wilcoxon test will be performed. It was found that 61 students had hypercholesterol and 36 of them had decreased to normal after consuming emprit ginger extract. This result is supported by statistical analysis using the Wilcoxon method with a p-value of 0.000 (p 0.05).  It can be concluded with a p-value of 0.000 that the administration of emprit ginger extract has the potential to have a significant influence on students suffering from hypercholesterolemi